2009
DOI: 10.3176/eng.2009.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Application of the indentation method for cracking resistance evaluation of hard coatings on tool steels

Abstract: In this paper cracking resistance and fatigue properties of five hard coatings-TiN, TiCN, TiAlN, AlTiN and nanocomposite nc-AlTiN/a-Si 3 N 4 (nACo®) on tool steels Weartec TM and Vanadis 6 are evaluated by means of the cyclic Vickers indentation method. The analytical part covers an evaluation of damage evolution of the coated system versus the number of cycles. The comparative adhesion testing was conducted with the use of the Rockwell C technique. It was found that the type of cracks formed in the coated sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The fracture toughness value for TiN closely matches within the range 2 to 7 MPa.m 0·5 reported by others. 44 It is reported elsewhere 45 that the coatings with lower E/H ratios, as that of nc-TiAlN/a-Si 3 N 4 , are prone to more cracking due to brittle damage (tensile driven cracking), while coatings with higher E/H ratios such as TiN are prone to quasi-plastic damage (shear driven cracking). Hence, such fracture toughness values for two different coatings are quite reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…The fracture toughness value for TiN closely matches within the range 2 to 7 MPa.m 0·5 reported by others. 44 It is reported elsewhere 45 that the coatings with lower E/H ratios, as that of nc-TiAlN/a-Si 3 N 4 , are prone to more cracking due to brittle damage (tensile driven cracking), while coatings with higher E/H ratios such as TiN are prone to quasi-plastic damage (shear driven cracking). Hence, such fracture toughness values for two different coatings are quite reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…For example, surface radial cracks which grow gradually extend from the impact zone with an increasing number of cycles and/or load. In cyclic Vickers indentation of hard coatings on tool steels, the observed crack morphology around the indent was found to depend on the H/E ratio of the coatings [78]. A quasi-plastic damage mode with radial cracks that increased in length under continued cyclic loading was found in coatings with relatively lower H/E [78].…”
Section: Impact Fatigue Mechanismsmentioning
confidence: 92%
“…In cyclic loading of brittle ceramics with spherical tungsten carbide indenters radial cracks were observed that were absent in single loading [33]. In cyclic Vickers indentation of hard coatings on tool steels the type of cracking depended on the H/E ratio of the coatings [80]. A quasi-plastic damage mode with radial cracks that grew with number of cycles was typical in lower H/E coatings.…”
Section: Impactmentioning
confidence: 98%